ARRANGING THE RHYTHM OF ROYALTY OBLIGATIONS IN THE BROADCASTING OF SONGS AND MUSIC BY LOCAL RADIO IN MEDAN CITY - Devi Azwar, T. Keizerina; Siagian, Putri Rumondang; Desiandri, Yati Sharfina; Arifiyanto, Joiverdia; M. Wau, Hilbertus Sumplisius (NOMOI Law Review, 2025)
Local radio stations play a vital role in the broadcasting industry, serving as a key platform for sharing information and entertainment with the community. However, as the digital music industry continues to evolve, local radio stations in Medan face increasingly complex challenges in complying with copyright laws for songs and music. This study explores the struggles of local radio stations in meeting royalty payment obligations while also examining the regulatory and economic barriers that impact the enforcement of copyright laws in the broadcasting sector. Using a juridical-normative approach with qualitative methods, this research conducts a case study of several local radio stations in Medan. The findings reveal that although awareness of royalty obligations is growing, significant challenges remain. These include unclear regulations, financial burdens, and a lack of understanding of how royalties are distributed. This study highlights the need for greater collaboration between the government, collective copyright management organizations, and radio industry players to establish a fairer and more sustainable system for ensuring compliance with music copyright laws in local broadcasting.